TERRESTRIAL MOLLUSC SUCCESSION AND STRATIGRAPHY OF A HOLOCENE CALCAREOUS TUFA DEPOSIT FROM THE FYLEDALEN VALLEY, SOUTHERN SWEDEN - Gedda B. (My University, 2006)
A Holocene calcareous tufa deposit in the Fyledalen Valley in southern Sweden was investigated with respect to molluscs, pollen, plant macrofossils and Coleoptera remains. The investigation recovered four mollusc species that today are severely threatened and included in the Swedish Red List of Endangered Species and/or the European Community’s Natura 2000 programme. These include Vertigo genesii (Gredler), Vertigo geyeri Lindholm, Cochlicopa nitens (Gallenstein) and Vertigo moulinsiana (Dupuy). Tufa formation was initiated in the early Preboreal (after 11 500 cal. BP), when an open birch-pine forest dominated the area and stopped in the late Boreal (after 8800 cal. BP) when deciduous trees had become established. The presence of the molluscan species Vallonia pulchella (MUller), Columella columella (Martens), Vertigo genesii, Pupilla muscorum (L.) and Euconulus alderi (Gray), coupled with an almost complete lack of shade-demanding taxa, suggests an open marsh environment throughout the time of tufa deposition. The mollusc succession shows evidence of increasing temperature. Columella columella, commonly associated with open arctic-alpine habitats is present at the base of the profile in the early Preboreal, whilst Vertigo genesii, which commonly is associated with open arctic-alpine habitats or calcareous springs, persists until the mid-Boreal (? 8800 cal. BP). The tufa deposition ends when the regional groundwater levels rise, approximately 8800 cal. BP, more thermophilous molluscs, such as Vertigo moulinsiana and V angustior Jeffreys and the aquatic Bithynia tentaculata (L.), Radix peregra (MUller) and Planorbis planorbis (L.) colonize the site. Stratigraphic correlations, as well as faunal and floral comparisons, are made with nearby sites.
Keywords: TUFA; MOLLUSCA; BIOSTRATIGRAPHY; POLLEN; SUCCESSION; CLIMATE; CONSERVATION; LANDSCAPE CHANGE; SWEDEN; SKANE; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен